Estratégias para o desenvolvimento de programa de colheita de sementes de sucupira-preta (Bowdichia virgilioides Kunth.) em Mata Atlântica do Recôncavo da Bahia - Almeida, Daiane Sampaio (2018)
The intense exploratory process of forest species such as sucupira-preta (Bowdichia virgilioides Kunth.). A native species of great economic and environmental potential, found in degraded areas and indicated for reforestation, causes a continuous pressure on the native forests causing fragmentation of the remnants, necessitating information on species that may aid in the recovery of these areas. In the search for the development of a program of seed collection of the species where the analysis of the spatial distribution, genetic diversity, phenology, route optimization and harvest planning and seed quality was carried out in 167 individuals, 32 matrices, 6 populations in the Atlantic Forest of the Bahia Recôncavo. In general, a distribution pattern of B. virgilioides tending to be non-grouped, in smaller plots, and grouped, may be observed for larger plots. The aggregate spatial distribution pattern of B. virgilioides populations was altered in relation to native forests because they were found in small fragments and / or as remnants in pasture or cultivated areas. It was verified the existence of low genetic diversity between the populations, when based on phenotypic characters, indicating that the evaluated genotypes are part of a single population that was fragmented. Phenology evidenced populations with annual reproductive cycle and intermediate duration. The low synchrony allied to the low intensity of phenophasis, more specifically, fruiting and dispersion requires attention on the quantity of seeds needed, besides observation of the harvesting period, which should be from january to may, in order to maintain quality. The information should integrate the database for use in further research and seed collection programs of the species. The use of software has shown to be very promising for actions of forest harvesting, and can be extended to other by-products, mainly for logistic companies and institutions that use road transport in their research, always supported in the correct planning of the field actions, and answered as access the harvesting areas less so. It was observed that the seeds presented with quality, among other parameters, reaching 80.33% of emergence. The knowledge of the physical and physiological characteristics of the seeds can help in the selection of populations with seeds of higher physiological potential that offer more uniform seed lots, with higher quality and are more likely to be established in environments with adverse conditions. can subsidize the choice of native populations and collaborate in seed harvesting programs for reforestation. The study provides complete information about native forest seeds, which can help the development of the species' harvest program, as well as the decolumnization of forest research and Brazilian silviculture. For all the decisions taken in the present work, the aim was to adapt the methodologies so that they could be reproduced by those who did not have as many technical tools as in the selection of matrices, the harvesting and determination of the quality, making the results of the research can be applied to those who need it in a practical way. Thus, the results obtained for the species may be a good parameter for programs to obtain seeds of other forest species of Bahia, which can also produce seedlings for reforestation in the state, also help the conservation of the species, and perhaps even fragmented areas.